Correlating dislocation mobility with local lattice distortion in refractory multi-principal element alloys. (1st January 2023) - Chen, Bing; Li, Suzhi; Ding, Jun; Ding, Xiangdong; Sun, Jun; Ma, En
Abstract: Multi-principal element alloys (MPEAs) exhibit different degrees of intrinsic lattice distortion, which varies with constituent species. Using atomistic simulations, here we found the mobilities of both edge and screw dislocations are dependent on lattice distortion in body-centered-cubic (BCC) MPEAs. Lattice distortion influences not only the activation of kink nucleation and propagation governing screw dislocation motion, but also the strength of local pinning for edge dislocations. As a consequence, the disparity between the velocities of screw and edge dislocations decreases with increasing lattice distortion. We further demonstrate that lattice distortion can be taken as an indicator to correlate with the reported brittleness of BCC MPEAs. This implies that maximizing lattice distortion could be a plausible strategy to improve the ductility for brittle BCC MPEAs. Graphical abstract: Image, graphical abstract